MANAJEMEN E-GOVERNMENT DI KECAMATAN BUKIT RAYA KOTA PEKANBARU TAHUN 2018 - Islami, Akbar; Tinov, M. Y. Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Bukit Raya Subdistrict is the only subdistrict in Kota Pekanbaru which first innovate in terms of E-Government that follows the presidential Instruction No. 3 year 2003 about E-Government. It is also aligned with the vision and mission of Pekanbaru City to the civil city of Smart City. E-Government in Bukit Raya subdistrict started in July in 2017. This E-Government management has several stages in managing it, preparation phase, maturation stage, maturation stage and utilization stage. There are several theories, one of which is E-Goverment In Action by Richardus Eko Indrajit (2005:5) explaining the vision that proclaimed also should reflect the shared vision of the existing stakholeder, improving productivity and operational performance Government in serving its community, promoting clean and transparent government, improving the quality of people's lives through the performance of public services, ensuring the creation of a democratic state. This research uses a descriptive method with a qualitative type of research by conducting interviews and documentation in the field. Here are some applications of E-Government of Bukit Raya Kota Pekanbaru is integrated system of administration Services (Sipadu), E-Sapa residents, integrated Administration services System (snail), strategic database, E-PPBMRW, E-MTQ, website District.            Research results seen E-Government management in Bukit Raya Kota Pekanbaru in the year 2018 can be concluded, that has been done with maximum. With the phenomenon of E-Government management in Bukit Raya City Pekanbaru District, among others, there is no full support from Pekanbaru city government such as socialization and budget as well as the absence of experts or escort team of city government Pekanbaru. E-Government provides more effective and efficient administration management & Information disclosure on the way government system. Bukit Raya became the best district for the last 3 years in the performance of Pekanbaru city level.  Results in the starting field of August 2017 to 2018, now starting to optimal according to the field findings with a cooperation of 2,725 letters through Sipadu (E-Government) previously only done by manual can work on 627 Surat.  Factors affecting E-Government management in Bukit Raya District Pekanbaru is the political environment, leadership, planning, transparency, stakeholders, finance, technology and innovation. Keywords: Management, E-Government